2022
DOI: 10.3390/diagnostics12061446
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of CCTA-Derived Features to Predict MACEs in Stable Patients Undergoing Coronary Computed Tomography

Abstract: Clinical evidence has emphasized the importance of coronary plaques’ characteristics, rather than lumen stenosis, for the outcome of cardiovascular events. Coronary computed tomographic angiography (CCTA) has a well-established role as a non-invasive tool for assessing plaques. The aim of this study was to compare clinical characteristics and CCTA-derived information of stable patients with non-severe plaques in predicting major adverse cardiac events (MACEs) during follow-up. We retrospectively selected 371 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…CCTA has achieved the temporal and spatial resolution to be able to define the lumen of even distal segments of the coronary artery tree. For this reason, the use of NC-CCTA has become less prevalent with the development of new techniques [9] and recent studies have demonstrated the integration of plaque analysis tools and pericoronary fat inflammation (pFAI) as valuable additions to cardiovascular risk evaluation, allowing for better stratification of cardiac risk beyond the degree of anatomical CAD, even in nonsignificant plaques [10][11][12]. For example, pFAI was shown to have different temporal distributions in patients with acute myocardial infarction type 2 compared to those with myocardial infarction with non-obstructive coronary arteries [13,14].…”
Section: Comparison To Other Advanced Cardiac Compute Tomography Toolsmentioning
confidence: 99%
“…CCTA has achieved the temporal and spatial resolution to be able to define the lumen of even distal segments of the coronary artery tree. For this reason, the use of NC-CCTA has become less prevalent with the development of new techniques [9] and recent studies have demonstrated the integration of plaque analysis tools and pericoronary fat inflammation (pFAI) as valuable additions to cardiovascular risk evaluation, allowing for better stratification of cardiac risk beyond the degree of anatomical CAD, even in nonsignificant plaques [10][11][12]. For example, pFAI was shown to have different temporal distributions in patients with acute myocardial infarction type 2 compared to those with myocardial infarction with non-obstructive coronary arteries [13,14].…”
Section: Comparison To Other Advanced Cardiac Compute Tomography Toolsmentioning
confidence: 99%
“…[9][10][11] Detailed visualization of plaque components has allowed the identification of high-risk and vulnerable plaque features, which has led to the improvement in the prognostic power of the techinque. [12][13][14] Nowadays, the applications of the fractional flow reserve derived from CT (FFR ct ) and the stress CT perfusion (CTP) Article à Andrea Igoren Guaricci and Danilo Neglia contributed equally as first authors.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, current indications of CTA include a large spectrum of patients with suspected CAD 9–11 . Detailed visualization of plaque components has allowed the identification of high-risk and vulnerable plaque features, which has led to the improvement in the prognostic power of the techinque 12–14 . Nowadays, the applications of the fractional flow reserve derived from CT (FFR ct ) and the stress CT perfusion (CTP) allow the combination of anatomic and functional assessment of CAD with excellent diagnostic and prognostic accuracy (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary computed tomography angiography (CCTA) provides various tools with which to assess coronary artery disease, ranging from calcium scoring to coronary plaque analysis. These tools are utilized as comprehensive prognostic indicators (based on scores) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%